PENGARUH PENGUASAAN GAYA TERHADAP HASIL BELAJAR FISIKA MATERI POKOK USAHA DI KELAS XI SMA NEGERI 1 SIPIROK - Febriani Hastini Nasution (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
brain material masteryto studentlearning achievementof thephysic on material of effort at eleventh grade of SMA Negeri 1 Sipirok. The method of the research was descriptive method. The population was the eleventh grade students of science atSMA Negeri 1 Sipirok is divided in three parallel class.It consists of 120 students. Random sampling technique was done in this research. The sample of this research consists 30 students.Based on the analysis of the data, the average score of force mastery was 77,1. It can be categorized on “Good”. While the students achievement on material effortwas 82,5, in “very good” category.Ther-product moment was done to analysis of the data. tcountwas 7,722. While ttable was 2,05. It means that the tcount was higher than ttable(7,722> 2,05). In other words the hypothesis of this research was accepted. It means that there was the Effect of force mastery to studentlearning achievementof thePhysic on material of effortat eleventh grade of SMA Negeri 1 Sipirok.